Materialização do imaginário por meio da estética de próteses de membro superior - Caselas, Raissa Gonçalves (2018)
With the increasing insertion of 3D printing technologies in the industry, it becomes possible to develop new approaches for objects of different uses, allowing the creation of products highly adaptable to users, as well as the possibility of overcoming design barriers. Being aware of the limits of production and mechanical strength of materials as for lower limb prostheses when related to 3D printing, this research focused on the development of upper limb prostheses. Aiming to analyze the aesthetic and functional ways that the production of these prostheses has covered, were proposed case studies that sharpened the user's imagination and allowed them to be brought from the intangible to the palpable. Projects that were once considered to be impractical, with the technological advance are shown to be feasible, since CAD modeling with 3D printing opens new possibilities. Basing on the information sharing and using open source prosthesis designs, it was possible to attest to its reproducibility as well as the recurring aesthetic attributes, thus, two prostheses were printed and constructed with the use of additive manufacturing technology. Based on several authors from different areas, such as Lucia Santaella, Masahiro Mori, Vilem Flusser, João Teixeira, Chris Anderson and Kathryn Allan, as well as product development concepts, it was finally noticed that the aesthetics resulting from this union permeates the cyberpunk universe, introducing people who have physical disabilities not as "imperfect," but through technology, they can be like superhumans. Contrary to what was believed, prostheses showed a certain tendency towards robotization, admitting their inorganic nature and providing other means of personalization